CCDC88B is required for mobility and inflammatory functions of dendritic cells. Issue 6 (1st June 2020) - Olivier, Jean‐Frederic; Fodil, Nassima; Al Habyan, Sara; Gopal, Angelica; Artusa, Patricio; Mandl, Judith N.; McCaffrey, Luke; Gros, Philippe
Abstract: The Coiled Coil Domain Containing Protein 88B ( CCDC88B ) gene is associated with susceptibility to several inflammatory diseases in humans and its inactivation in mice protects against acute neuroinflammation and models of intestinal colitis. We report that mice lacking functional CCDC88B ( Ccdc88b Mut ) are defective in several dendritic cells (DCs)‐dependent inflammatory and immune reactions in vivo. In these mice, an inflammatory stimulus (LPS) fails to induce the recruitment of DCs into the draining lymph nodes (LNs). In addition, OVA‐pulsed Ccdc88b Mut DCs injected in the footpad do not induce recruitment and activation of antigen‐specific CD4 + and CD8 + T cells in their draining LN. Experiments in vitro indicate that this defect is independent of the ability of mutant DCs to capture and present peptide antigen to T cells. Rather, kinetic analyses in vivo of wild‐type and Ccdc88b Mut DCs indicate a reduced migration capacity in the absence of the CCDC88B protein expression. Moreover, using time‐lapse light microscopy imaging, we show that Ccdc88b Mut DCs have an intrinsic motility defect. Furthermore, in vivo studies reveal that these reduced migratory properties lead to dampened contact hypersensitivity reactions in Ccdc88b mutant mice. These findings establish a critical role of CCDC88B in regulating movement and migration of DCs. Thus, regulatory variants impacting Ccdc88b expression in myeloid cells may cause variable degrees of DC‐dependent inflammatory response in situ, providing a rationale for the genetic association of CCDC88B with several inflammatory and autoimmune diseases in humans. Graphical Abstract: CCDC88B has a critical role in regulating dendritic cells' motility, impacting their ability to migrate to the lymph nodes and dampening inflammatory and immune reactions.